A Simple and Versatile Method for the Construction of Nearly Ideal Polymer Networks. (6th April 2020) - Huang, Xin; Nakagawa, Shintaro; Li, Xiang; Shibayama, Mitsuhiro; Yoshie, Naoko
Abstract: Polymer networks usually contain numerous inhomogeneities that deteriorate their physical properties and should be eliminated to create reliable, high‐performance materials. A simple method is introduced for the production of nearly ideal networks from various vinyl polymers through controlled polymerization and subsequent crosslinking. Monodisperse star polymers with bromide end groups were synthesized by atom‐transfer radical polymerization and end‐linked with dithiol linkers using thiol–bromide chemistry. This simple procedure formed nearly ideal polymer networks, as revealed from elasticity of the formed gel and model conjugation reactions involving linear polymers. The versatility of this method was demonstrated by preparing networks of common vinyl polymers, including polyacrylates, polymethacrylate, and polystyrene. This method can be used to prepare multiple functional nearly ideal gels and elastomers and to explore fundamental aspects of polymer networks. Abstract : Almost perfect : A simple and versatile method to fabricate nearly ideal polymer networks from a wide variety of vinyl monomers was established by combining atom‐transfer radical polymerization and thiol–bromide click chemistry. This method significantly widens the application scope of nearly ideal networks.